Rinikerfeld Palaeolake (Northern Switzerland) – a sedimentary archive of landscape and climate change during the penultimate glacial cycle. (16th August 2022) - Gegg, Lukas; Anselmetti, Flavio S.; Deplazes, Gaudenz; Knipping, Maria; Madritsch, Herfried; Mueller, Daniela; Preusser, Frank; Vogel, Hendrik; Buechi, Marius W.
Abstract: While timing and ice extent of the last glacial maximum are generally well known, the courses of earlier glaciations have remained poorly constrained, with one of the main reasons being the scarcity of sedimentary archives. This study introduces a new palaeolake record from a Mid‐Pleistocene glaciofluvial channel system in the Lower Aare Valley (Northern Switzerland). The record of Rinikerfeld comprises a >40 m long succession of Quaternary deposits that are targeted by multi‐method sedimentological analysis. Sedimentary facies together with geochemical and geotechnical parameters, pollen content, as well as luminescence ages allow the reconstruction of the establishment, evolution and infilling of the early Marine Isotope Stage 6‐aged Rinikerfeld Palaeolake. A drastic change in lake sediment composition and structure indicates cessation of the initial glacially derived input, which is explained by landscape modification and drainage rerouting during the Penultimate (Beringen) Glaciation. Geochemical and palynological data further reveal cold, initially periglacial but slightly ameliorating, climate conditions, while the lake was progressively filled up by local runoff, before being buried by periglacial colluvial diamicts, and potentially overridden by ice. It is therefore concluded that the onset of the Beringen Glaciation was an environmentally as well as geomorphically dynamic time period in the Northern Alpine Foreland.